Wages and Hours: Labor and Reform in Twentieth-Century America - Dubofsky, Melvyn (Labour / Le Travail, 1984)
This article reviews the book, "Wages and Hours: Labor and Reform in Twentieth-Century America," by Ronnie Steinberg.